The awareness of the IPTA student in Sabah toward Sabah tourism board as a state government tourism promotional agency / Franklin Hazley Lai - Lai, Franklin Hazley (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2006)
The researcher may conclude that the IPTA students in Sabah mostly aware of the existence of Sabah Tourism Board (STB). However, the functions of the company were not widely known. Students may tend to generalize the functions according to the brand name. The major factor that contributes to the awareness is the internet/ radio. Billboards and event management may also contribute to the awareness but in a very limited way. In order for the students to get close with STB they need, STB to organize a trip for students to explore Sabah more clearly. For the promotional program which will help to improve the IPTA students’ awareness in the near future, the students would like to have tourism campaign to be held at their respective university. As a conclusion, IPTA students in Sabah agreed that STB has done a good job in promoting Sabah as a world class destination.